Epitaxial growth of wafer scale antioxidant single-crystal graphene on twinned Pt(111). (30th August 2021) - Kang, He; Tang, Pengtao; Shu, Haibo; Zhang, Yanhui; Liang, Yijian; Li, Jing; Chen, Zhiying; Sui, Yanping; Hu, Shike; Wang, Shuang; Zhao, Sunwen; Zhang, Xuefu; et al.
Abstract: Wafer-scale single-crystal graphene with strong antioxidation is fundamentally important for their applications in electronics and optoelectronics. Although significant progress has been achieved in the chemical vapor deposition (CVD) growth of graphene, the production of wafer-scale graphene with high crystalline and excellent oxidation resistance still remains a challenge. Here, we report the epitaxial growth of 6-inch single-crystal graphene on twinned Pt (111) films with in-plane rotation of 60°(T-Pt) by ambient-pressure CVD. Our results show that the CVD-grown graphene on T-Pt exhibits fast growth rate and ultrahigh stability under the high-temperature air condition (>500 °C). The density functional theory (DFT) calculations reveal that the twinned Pt(111) surface does not change the preferential orientation of graphene nucleation, leading to highly aligned graphene domains on the T-Pt substrate. Moreover, the edge growth of graphene cannot be limited by the Pt twin boundaries (TBs), which is responsible for the fast growth of graphene single crystals. This work provides a reliable route to produce wafer-size single-crystal graphene monolayers with excellent oxidation resistance and clarifies the oriented growth mechanism of graphene domains on twinned Pt substrate. Graphical abstract: Here, we report an oriented multi-nuclei growth strategy toward 6-inch single-crystal graphene on twinned Pt (111) films with in-plane rotation of 60° (T-Pt) by ambient-pressure chemical vapor deposition. The graphene on Pt grows fast and has better oxidation resistance than graphene on Cu substrate. The density functional theory (DFT) calculations reveal that Pt-twinned structure does not change the preferential orientation of graphene nuclei, resulting in highly oriented graphene domains on the T-Pt substrate. This work provides a reliable approach to produce wafer-size single-crystal graphene monolayers with excellent oxidation resistance and clarifies the oriented growth mechanism of graphene domains on T-Pt substrate. Image 1